Boom, bust, and the lack of trust: when stakeholder priorities collide. (25th November 2019) - Subramanian, Ram; Tichenor, John M.
SMI Companies Global Inc., a Louisiana-based contract manufacturer for the oil and gas industry had a conflict with Whitney Bank regarding a line of credit. The line of credit was for a specific contract to supply acid storage tanks to Halliburton. Due to a series of delays on the part of Halliburton, the contract was started much later than originally envisaged. While the bank was aware of the delays, they were unwilling to extend the time for the repayment of the loan. Vaughn S. Lane, the founder and owner of the company, learned that the bank had, unilaterally and quite abruptly, turned the loan over to the bank's attorney for collection. He had to make a decision as to how to respond to the expected call from the attorney.